EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DAN STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) DITINJAU DARI KEINGINTAHUAN DAN GAYA KOGNITIF PESERTA DIDIK SMP DI KABUPATEN BLORA - Wijaya, Agung Putra; Mardiyana, Mardiyana; Suyono, Suyono (Journal of Mathematics and Mathematics Education, 2011)
Â ABSTRACTThe purposes of this study are to know the different effect of each category of learning model, curiosity, and cognitive style, also their interaction towards mathematics achievement. This study is a quasi experimental research with 2x3x2 factorial design. The population is all students of junior high school in Blora. Sampling was done by stratified cluster random technique. The instruments used to collect data are test of prior knowledge in mathematics, curiosity questionnaire, cognitive style test (GEFT), and mathematics achievement test. The testing of hypothesis uses three-way analysis of variance with unequal cell. The testing of hypothesis concludes that (1) There is a different effect between each category of learning model. (2) There is a different effect among each category of curiosity. (3) There is a different effect among each category of cognitive style. (4) There is an interaction between learning model and curiosity towards mathematics achievement. (5) There is an interaction between learning model and cognitive style towards mathematics achievement. (6) There is an interaction between curiosity and cognitive style towards mathematics achievement. (7) There is an interaction among learning model, curiosity, and cognitive style towards mathematics achievement.Keywords: NHT, STAD, Curiosity, Cognitive Style, Mathematics Achievement